The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/vms3.515
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic anatomy, radiography and computed tomography of normal paranasal sinuses of the adult one‐humped dromedary (Camelus dromedarius)

Abstract: In order to improve the current knowledge of the topography and the anatomy of the paranasal sinuses of the one‐humped dromedary (Camelus dromedarius), we applied both conventional and advanced imaging techniques, namely, radiography and computed tomography (CT). Twelve heads of healthy dromedaries were used; eight heads were dissected to obtain skulls for the fenestration of the sinuses, two heads underwent anatomical sections, and two heads were imaged respectively by radiography and CT. Sinus fenestration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…20,29 Such openings can be easily determined by performing CT scanning (Figure 4A-B/a). The right and left frontal sinuses were separated by an interfrontal septum in cattle, 2,4 buffaloes, 20,29 Alcelaphus species, 33 camels, 13,14 Egyptian sheep, 18 and Ossimi Sheep. 17 However, in cattle, small openings can be found on the caudal part of the septum.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…20,29 Such openings can be easily determined by performing CT scanning (Figure 4A-B/a). The right and left frontal sinuses were separated by an interfrontal septum in cattle, 2,4 buffaloes, 20,29 Alcelaphus species, 33 camels, 13,14 Egyptian sheep, 18 and Ossimi Sheep. 17 However, in cattle, small openings can be found on the caudal part of the septum.…”
Section: Discussionmentioning
confidence: 99%
“…The ventral conchal sinus was reported in horses, 3,8,9,12 cattle, 2,3,21,27 pigs, 2,3,21,27 and goats. 19,21,28 However, the ventral conchal sinus is absent in buffaloes, 20 camels, 13,14 and Egyptian sheep. 18 In this study, we found that the ventral conchal sinus occupied the caudal part of the ventral nasal concha in 11 animals, one of which was unilateral (left) (Figures 2C-D,3A-B,7,8/VCS, Table S).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations